Synthesis, characterisation and luminescent properties of lanthanide-organic polymers with picolinic and glutaric acids - Girginova, Penka I. (2007)
Three new lanthanide(III) complexes (Ln = Sm, Tb and Eu) of picolinic and glutaric acid were prepared and characterised. The crystal structure of the complex [Sm(glu)(pic)- (H2O)2] (where Hpic and H2glu stand for picolinic and glutaric acid, respectively) was determined by single-crystal Xray diffraction. All the Ln complexes were characterised by elemental analysis, infrared spectroscopy, X-ray powder diffraction and thermoanalytical measurements. The combined Introduction The design of functional units from the molecular scale to macroscopic assemblies has emerged as a new paradigm in materials synthesis resulting in an interplay between conventional molecular chemistry and conventional solid-state science. This has been particularly clear in the development of functional materials using coordination compounds such as in the field of semiconductors technology, supramolecular machinery, microporous and hybrid materials and catalysis.[ 1] In some cases, the development of these functional materials is based on the chemistry of well-known coordination compounds as illustrated by the assembly of inorganic- organic extended lattices[2] and in the thermolysis of metal thiolato compounds to produce thin films or nanoparticles.[ 3] Metals coordinated to aromatic ambidentate ligands form a class of compounds with a wide variety of coordination modes which has long attracted the attention of chemists.[ 4] Griffith and co-workers extended this type of chemistry to the second row transition metals and, in particular, [a] Department of Chemistry, University of Aveiro, CICECO, 3810-193 Aveiro, Portugal Fax: +351-234-370-084 E-mail: ttrindade@dq.ua.pt [b] Department of Physics, University of Aveiro, CICECO, 3810-193 Aveiro, Portugal [c] Department of Chemistry, University of Cambridge, Lensfield Road, CB2 1EW Cambridge, United Kingdom Supporting information for this article is available on the WWW under http://www.eurjic.org or from the author. © 2007 Wiley-VCH Verlag 4238 GmbH & Co. KGaA, Weinheim Eur. J. Inorg. Chem. 2007, 4238–4246 data show that these Ln complexes are isostructural. The effect of both organic ligands on the photoluminescent behaviour of the Sm3+, Eu3+ and Tb3+ complexes is discussed and we anticipate the possibility of controlling the photoluminescence of picolinic-containing lanthanide compounds by systematically varying the length of the bridging ligand.